Institutional Capacity Building of Art Studios and Digital-Based Cultural Promotion in Solok Selatan Regency - Khairunnisa, Khairunnisa; Erwin, Muhammad Syukri Erwin; Faradhiga, Aryadwipa A. Faradhiga; Wijaya, Okza Hendrian; Fabianti, Dian Marsyah (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2025)
Institutional capacity strengthening and the utilization of digital technology for the promotion and documentation of artworks are among the main challenges faced by art studios in Solok Selatan Regency. This community service program aims to enhance the organizational management of art studios and improve the digital skills of artists through training sessions that cover institutional management, art event planning, and the use of social media, photography, and videography for art promotion.The program began with an analysis of the current situation and the challenges faced by the art studios, followed by the design of training activities tailored to local needs. The results of the program show that the training successfully improved participants’ abilities in managing their organizations and utilizing digital technology to expand the reach of their art promotion. Although there were challenges related to limited technology access and low levels of digital literacy, collaboration among local government, educational institutions, and art communities is expected to support the program’s sustainability. Overall, this program made a significant contribution to the development of local arts and culture while encouraging the growth of the creative economy in Solok Selatan Regency.